Agriculture, Trade, and the WTO : Creating a Trading Environment for Development - Ingco, Merlinda D. (Washington, DC: World Bank, 2013)
Developing countries have an enormous stake in the new round of World Trade Organization (WTO) negotiations, taking place now, and scheduled to be completed by January 1, 2005. Their full participation in the global trading system could lift and additional 300 million people our of poverty by 2015. Since 1970, these countries have increased their share in all trade, from one-quarter to one-third. Most of these gains, however, have come from increased exports of manufactured goods, which primarily benefit the middle-income developing countries. Agricultural products, historically the more important exports for poor countries, have lagged far behind. The main reason for this is the protection - in the form of subsidies and other support, running at roughly U$S 1 billion per day - afforded agriculture in industrial countries. This is more than six times all development assistance. This report contains results of region-specific studies that will prove a vital resource for policymakers, analysts, and others working in the development field. It provides answers to questions such as, What lessons were learned from the Uruguay Round? What is the relationship between trade liberalization, and rural poverty? And, What is the role of the international development community in fostering a trading system that will result in development? The authors argue that only by reshaping the world's trading system, and reducing the barriers to trade, can truly global expansion take place.